Evaluation of the Leadership Capabilities Model for Organizational Service Productivity (Case Study: Public Banking Sector in Iraq) - Abdali, Qasim Mohammed; Aghasi, Saeid; Amanah, Ahmed Abdullah; Davoodi, Sayyed Mohammad Reza (Management Strategies and Engineering Sciences, 2024)
The aim of this research is to evaluate the leadership capabilities model for organizational service productivity, with a focus on the public banking sector in Iraq. This research is applied in nature and descriptive-correlational in method. The statistical population of the study consists of senior and middle managers of state-owned banks in Iraq, totaling 217 individuals. Using Cochran's formula, the sample size was calculated to be 138 individuals. The sample was selected randomly. The data analysis tool used is a standardized questionnaire, and the software for data analysis is PLS. The results indicate that leadership capabilities, with components such as possessing strategic visions, having effective organizational communication, team management and leadership skills, having appropriate personality traits, focusing on customer needs, the ability to facilitate changes, and having decision-making power, are significantly related (t_value > 1.96). The overall model fit, based on the GOF formula, was found to be 0.59, which indicates a strong fit.